2011
DOI: 10.1016/j.cub.2011.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Hypersynchrony Predicts Breakdown of Sensory Processing during Loss of Consciousness

Abstract: Intrinsic cortical dynamics modulates the processing of sensory information and therefore may be critical for conscious perception. We tested this hypothesis by electroencephalographic recording of ongoing and stimulus-related brain activity during stepwise drug-induced loss of consciousness in healthy human volunteers. We found that progressive loss of consciousness was tightly linked to the emergence of a hypersynchronous cortical state in the alpha frequency range (8-14 Hz). This drug-induced ongoing alpha … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
135
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(165 citation statements)
references
References 45 publications
(81 reference statements)
22
135
0
Order By: Relevance
“…A variety of EEG patterns are known to arise during GA maintained by both GABA A receptor-specific and ether-derived anesthetics. These EEG patterns include increases in frontal EEG power (20)(21)(22)(23)(24), a shift in EEG power toward lower frequencies (25), changes in coherence (22,26), and burst suppression and isoelectricity (27). However, the relationship between these or other EEG patterns…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of EEG patterns are known to arise during GA maintained by both GABA A receptor-specific and ether-derived anesthetics. These EEG patterns include increases in frontal EEG power (20)(21)(22)(23)(24), a shift in EEG power toward lower frequencies (25), changes in coherence (22,26), and burst suppression and isoelectricity (27). However, the relationship between these or other EEG patterns…”
mentioning
confidence: 99%
“…To minimize spatial blurring in this and subsequent analyses, we used a nearest-neighbor Laplacian reference, in which the Laplacian is calculated by taking each channel and subtracting the average of the nearest neighbors (24). During induction, gamma (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) and beta (13-24Hz) power increased significantly above baseline levels during the 30 min before LOC-when P clicks < P verbal -and remained elevated during the unconscious period ( Fig. 2 B and C).…”
Section: Dynamics Of the Eeg Spectrum Covary With Changes In Probabilmentioning
confidence: 99%
“…Electroencephalogram (EEG) recordings in humans during gradual induction of unconsciousness with propofol show the appearance of frontal β oscillations (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) at the onset of sedation, followed by the appearance of coherent frontal α (8-12 Hz) oscillations (7)(8)(9)(10) and widespread slow (0.1-1 Hz) and δ (1-4 Hz) oscillations (7,11,12) when subjects no longer respond to sensory stimuli. Biophysical models of neuronal dynamics have shown that whereas α and β oscillations can be generated by propofol's actions in cortex alone (13), coherent α oscillations require the participation of both thalamus and cortex (14).…”
mentioning
confidence: 99%
“…Additional support for this idea comes from the finding that the activity of cortical neurons appears to be highly synchronised in the anaesthetised brain, similar to the state they are in during SWS (Supp, Siegel, Hipp, & Engel, 2011). This is shown by ongoing low-frequency activity in the EEG signal during progressive loss of consciousness following the administration of increasing doses of a general anaesthetic (Supp et al, 2011). Synchronous firing therefore appears to be a common phenomenon in these two conditions characterised by diminished consciousness.…”
Section: Effective Connectivity Studiesmentioning
confidence: 58%
“…Similar results to those seen in NREM sleep were obtained in some disorders of consciousness (Rosanova et al, 2012; discussed below) and in general anaesthesia ; this has led to the suggestion that a breakdown of effective connectivity is characteristic of states of reduced consciousness in general . Additional support for this idea comes from the finding that the activity of cortical neurons appears to be highly synchronised in the anaesthetised brain, similar to the state they are in during SWS (Supp, Siegel, Hipp, & Engel, 2011). This is shown by ongoing low-frequency activity in the EEG signal during progressive loss of consciousness following the administration of increasing doses of a general anaesthetic (Supp et al, 2011).…”
Section: Effective Connectivity Studiesmentioning
confidence: 58%